Implementasi Desain Tempat Sampah Ergonomis di PT Pacific Place Mall - Nursetyowati, Prismita; Jachryandestama, Raden; Hartono, Gunawarman; Fanya, Annissa; Vabiano, Almindo; Safira, Salwa; Kurnia Dewi, Kadek (LPkM Universitas Bakrie, 2023)
One of the biggest contributors to the waste that goes into the Bantargebang TPST comes from areas and companies in DKI Jakarta. Therefore, the DKI Jakarta Government passed Governor Regulation No. 102 of 2021 concerning Obligations for Waste Management in Areas and Companies. With this Governor's Regulation, the waste bins not only meet the Governor's Regulation criteria but also must meet ergonomic standards to facilitate the sorting process. Pacific Place is one of the areas whose existing waste bins did not meet the criteria set by the Governor's Regulation, and segregation at the source was still ineffective, so it still must be re-sorted. As part of the Community Service, the team designed and provided ergonomic waste bins for sorting and provided socialization of a sorting system according to the Governor's Regulation. Prior to manufacturing ergonomic bins, a series of Focus Group Discussions (FGD), independent work, waste sampling, prototype trials, and socializations were carried out. Ergonomic waste bins have been designed according to Pacific Place requirements and comply with the Governor Regulation regulations and have high waste segregation efficiency with a 95-100% waste capture rate and 0-5% waste contamination rate for each type of waste bin tested: easy to decompose, recyclables and residue. The final product will be implemented in high-traffic areas so that it can also be an educational tool for Pacific Place visitors. With this implementation, Pacific Place is expected to contribute to reducing greenhouse gases from DKI Jakarta's solid waste sector and implementing the Sustainable Development Goals (SDGs).